Antibody Therapy Targeting CD47 and CD271 Effectively Suppresses Melanoma Metastasis in Patient-Derived Xenografts - Michael Ngo; Arum Han; Anita Lakatos; Debashis Sahoo; Stephanie J. Hachey; Kipp Weiskopf; Andrew H. Beck; Irving L. Weissman; Alexander D. Boiko (Cell Reports, 2016)
The high rate of metastasis and recurrence among melanoma patients indicates the existence of cells within melanoma that have the ability to both initiate metastatic programs and bypass immune recognition. Here, we identify CD47 as a regulator of melanoma tumor metastasis and immune evasion. Protein and gene expression analysis of clinical melanoma samples reveals that CD47, an anti-phagocytic signal, correlates with melanoma metastasis. Antibody-mediated blockade of CD47 coupled with targeting of CD271+ melanoma cells strongly inhibits tumor metastasis in patient-derived xenografts. This therapeutic effect is mediated by drastic changes in the tumor and metastatic site immune microenvironments, both of whichwhich exhibit greatly increased density of differentiated macrophages and significantly fewer inflammatory monocytes, pro-metastatic macrophages (CCR2+/VEGFR1+), and neutrophils, all of which are associated with disease progression. Thus, antibody therapy that activates the innate immune response in combination with selective targeting of CD271+ melanoma cells represents a powerful therapeutic approach against metastatic melanoma.